Effect of Cognitive Demand on Functional Mobility in Ambulatory Individuals with Multiple Sclerosis - Ciol, Marcia Aparecida (Int J MS Care, 2017)
BACKGROUND: As disease progresses, cognitive demands may affect functional mobility in individuals with multiple sclerosis (MS). The Timed Up and Go (TUG) test assesses functional mobilityin populationssuch as MS. A cognitive-demanding task can be added to the TUG test to assess its effect on functional mobility. METHODS: People with MS (n = 52) and controls (n = 57) performed three versions of the TUG test: TUG alone (TUG-alone), TUG plus reciting the alphabet (TUG-alpha), and TUG plus subtracting numbers by 3s (TUG-3s). Times to complete the TUG tests were compared among controls and three groups of participants with MS created using Expanded Disability Status Scale (EDSS) scores 0 to 3.5, 4.0 to 5.5, and 6. Differences among groups were analyzed using split-plot analysis of variance. RESULTS: Group and TUG type were significant (P < .001 for both), with no interaction effect of group × TUG type (P = .21). Mean times were 8.7, 9.4, and 11.1 seconds to perform the TUG-alone, TUG-alpha, and TUG-3s, respectively. Mean times for groups were 8.0, 8.2, 11.1, and 11.6 seconds for controls and individuals with MS and EDSS 0 to 3.5, 4.0 to 5.5, and 6, respectively. CONCLUSIONS: People with MS with an EDSS score greater than 3.5 had a statistically significant reduction in performance of the TUG test even with the addition of a simple cognitive task, which might have implications for a person's more complex everyday activities.